Handbook for SAP PP in S/4HANA : production planning and execution in SAP S/4HANA - Goel, Himanshu, 1989- (Apress, 2022)
If you're looking to increase your knowledge of one of the core modules of SAP S/4HANA, this is the book for you. Settle in and let a long-time SAP professional guide you through the SAP Production Planning and Execution module. Author Himanshu Goel begins by explaining the nuts and bolts of production planning in SAP S/4HANA, before delving into various manufacturing methodologies such as discrete manufacturing, repetitive manufacturing, and process industry. He'll then walk you through setting up master data such as the material master, bill of material, work center, routing, and production version. You'll then learn, step-by-step, how SAP PP processes are established from production order-based manufacturing to process order-based manufacturing. This book explains the complex concepts of production planning and execution in a straightforward manner and makes for an invaluable guide for SAP PP users from production planners to shop floor managers and even junior/mid-level SAP PP consultants. After reading this book, you'll fully understand the concepts of SAP PP, and have insight into the latest developments in S/4HANA.